The emergence and development of 'Beautiful Things' craft project in the inner city of Johannesburg - Ndlovu, Morgan (My University, 2007)
The emergence and development of tourism attractions in inner cities throughout the world has given rise to a number of scholarly debates in the academic study of urban tourism. While academic scholarship in the field of urban tourism began with the cities of the developed states mostly in the 1980s, the emergence and development of tourism initiatives in the inner cities of the developing states in 1990s has drawn a great deal of attention to the South as well. This research explores the emergence and development of an inner city tourism initiative in the form of a craft project known as Beautiful Things. Beautiful Things is a two-year-old craft project located at Newtown’s Cultural Precinct, in the inner city of Johannesburg. The project was inaugurated at the World Summit on Sustainable Development in August 2002, and has since its relocation to the inner city of Johannesburg in December 2002, contributed significantly to the physical, social and economic regeneration of this area. The study of this project is very important in that it is shedding some light on the role of heritage and cultural industries in rejuvenating declining inner cities. It gives light on how Newtown Cultural Precinct as a whole functions within the inner city of Johannesburg. In spite of this project’s role in the development of the Johannesburg inner city, Beautiful Things has not yet been explored for academic research. This research on Beautiful Things is set to be informative on a number of theoretical issues underpinning the development of urban heritage and cultural tourism in general and the development of tourism in Johannesburg. The findings of the study of Beautiful Things hopes to reveal important international trends on the development of heritage and cultural attractions in inner cities and to elucidate a number of similarities in the development of tourism policies across the cities of the world. This research begins with a chapter on the international experiences of heritage and cultural tourism developments in inner cities and is then followed by a study of Johannesburg’s tourism policy and strategy developments. Both chapters are vital in providing the context under which Beautiful Things came to emerge in the inner city of Johannesburg, performing an important role of regenerating the declining inner city. The last part of this research is an empirical confirmation study of physical, social and economic contributions of Beautiful Things in the inner city of Johannesburg. The research is informed by theories of neo-liberalization, local economic development, and inner city regeneration.
Morgan Ndlovu, Student no 0000141H, MA thesis, School of Arts, Faculty of Humanities, 2006. email: mn59@sussex.ac.uk
Keywords: Beautiful things craft project; craft project; inner city; regeneration; tourism initiative; urban tourism